Pengelolaan Hutan Berbasis Masyarakat (PHBM) Sebagai Upaya Pengakuan Hak Masyarakat Adat - Aminah (Law Faculty of Universitas Bandar Lampung, 2011)
The community based forest management Â as a recognition of rights of indigenous peoples effort, community based forest management is a form of cooperation between PT.Perhutani, people in forest, and stakeholder The concept is based on the values of Pancasila, among others: the value of the Godhead (religion morality), human values (humanistic) and social values (nationalistic, democratic and social justice). The community based forest management, im implementation can be felt to produce a double benefit, among others accommodated all interests: PT.Perhutani, forest society, is able to reduce conflicts of interest. The community based forest management can be regarded as a form of recognized of indigenous rights efforts, although limited to the recognition of forest resources management rights. Nevertheless, can be increasing forest society welfare.